Most Effective Regimen of Tranexamic Acid for Reducing Bleeding and Transfusions in Primary Total Knee Arthroplasty: A Meta-Analysis of Randomized Controlled Trials - Dai, Wen-Li; Zhou, Ai-Guo; Zhang, Hua; Zhang, Jian (The Journal of Knee Surgery, 2018)
The use of tranexamic acid (TXA) during primary total knee arthroplasty (TKA) is well documented. However, considering the potential side effects, including deep vein thrombosis (DVT) and pulmonary embolism (PE), the ideal route of administration remains controversial. Therefore, we performed a meta-analysis to compare the efficacy of topical versus intravenous TXA and explore the most effective regimen in patients undergoing primary TKA. We conducted a systematic literature search in PubMed, Embase, and the Cochrane database through July 2016 to identify randomized controlled trials (RCTs) evaluating the efficacy and safety of topical and intravenous TXA in primary TKA. We assessed the risk of bias using the Cochrane Collaboration's tool. We assessed the quality of evidence using the GRADE profiler software. A total of 15 RCTs including 1,240 participants met the inclusion criteria. We found no statistically significant difference between topical and intravenous TXA in terms of transfusion rate (p = 0.75), total blood loss (p = 0.51), total drain output (p = 0.60), maximum hemoglobin drop (p = 0.24), length of stay (p = 0.08), and thromboembolic complications (p = 0.73). Subgroup analyses showed that compared with 1 g topical TXA, 2 g topical TXA was more effective to reduce blood transfusion rate and total blood loss, and did not increase thromboembolic complications. We also found three times intravenous TXA was more effective than one time of intravenous TXA to reduce blood transfusion rate and total blood loss without increasing of thromboembolic complications. Topical TXA had a similar efficacy to intravenous TXA in reducing blood transfusion and blood loss, and did not increase the risk of thromboembolic complications in primary TKA. Besides, the current meta-analysis suggested that three times of intravenous TXA is efficient and safe. We also recommended 2 g topical TXA instead of 1 g topical TXA because it was more efficient to reduce blood transfusion rate and total blood loss and did not increase thromboembolic complications.
Keywords: topical; intravenous; tranexamic acid; total knee arthroplasty; meta-analysis